The Effect of Mindfulness-based Intervention on Reducing Childhood Trauma Symptoms - Dwi Heppy Rochmawati; Wigyo Susanto (Global Medical & Health Communication (GMHC), 2025)
Childhood trauma is a complex mental health issue with long-term psychological and neurobiological consequences. This study aims to analyze the effect of a mindfulness-based intervention on five dimensions of childhood trauma: emotional abuse, physical abuse, sexual abuse, emotional neglect, and physical neglect. A quantitative quasi-experimental design with a pre-posttest approach was employed, involving 174 young adults aged 18–25 years, conducted at the Faculty of Nursing, Universitas Islam Sultan Agung, Semarang, in June 2025. Childhood trauma symptoms were measured using the validated Childhood Trauma Questionnaire, while the intervention was delivered using an 8-week mindfulness-based stress reduction (MBSR) protocol modified with a trauma-informed framework. Data were analyzed using the Wilcoxon signed-rank test to assess differences in trauma scores before and after the intervention. The results revealed highly significant reductions in emotional abuse, physical abuse, and emotional neglect (p=0.000), as well as a significant reduction of sexual abuse (p=0.034). However, physical neglect did not show a significant change (p=0.166). The study concludes that mindfulness is effective in reducing the psychological impacts of childhood trauma through mechanisms of emotional regulation and enhanced interoceptive awareness. However, its effectiveness varies depending on the trauma subtype. This research contributes to the development of evidence-based trauma interventions and supports the integration of mindfulness within mental health care systems.